Green Human Resource: a New Perspective Green Recruitment, Employee Workplace Green Behavior and Green Training (Study Literature Review) - Dewi Susita; Jatmiko Murdiono (Greenation Research & Yayasan Global Resarch National, 2024)
This literature research aims to help future authors determine human resource management research. Green human resources research articles: new perspectives on green recruitment, green workplace behavior, and green training are scientific literature articles within the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique uses literature studies or reviews relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Recruitment affects Green Human Resources; 2) Employee Workplace Green Behavior affects Green Human Resources; and 3) Green Training affects Green Human Resources.